(untitled) (ArtCultura, 2007)
Este artigo se propõe a sintetizar as tendências e autores que marcaram a reflexão sobre a música popular no Brasil desde o final da década de 1970. Procuramos demonstrar a gênese da canção como tema de estudos acadêmicos, paralelamente ao reconhecimento sociocultural da música popular em fins dos anos 1960. Também ressaltamos os temas e perspectivas históricas mais destacadas ao longo dos vinte anos de produção analisados. Finalmente, apontamos algumas tendências e desafios heurísticos que envolvem o estado atual dos estudos sobre música popular no Brasil. PALAVRAS-CHAVE: música popular brasileira; historiografia; cultura brasileira. ABSTRACT The novel Le législateur moderne ou les mémoires du Chevalier de Meillcourt, written by Marquis d’Argens, published in 1739, presents philosophical reflexions, the adventures and mis-fortunes of Chevalier de Meillcourt, son of the count of the same name. He was educated according to a materialistic concept by his father, who fled to Holland and became Spinosa’s disciple. Meillcourt goes on voyage and sinks on the African coast, in the Indic Ocean, close to an island. In this island, he pacifies, colonizes and civilizes the people. He lectures on the relationship between the State, the society and the religion and at the same time he defends the religious tolerance and the monarchy. The book’s preface brings a violent critic against the colonization done by Spain and Portugal and, on the contrary, defends the English and Dutch colonizations. The purpose of this article is to study how the novel focuses on the Portuguese and the colonization, as well as its relationship with the Enlightenment thinking. KEYWORDS: novel; colonization; Marquis d’Argens.